Gender Inclusive Education in Preventing Sexual Violence in Islamic Boarding Schools - Intan Verly Syafitri; Firman; Dina Sukma (Konsultan Jurnal Ilmiah Indonesia, 2025)
Islamic boarding schools, as educational institutions that have an important role in forming the character and morals of students, are required to adopt a fair approach. This is important considering that sexual violence often stems from entrenched gender injustice and inequality. The aim of this article is to answer two central questions: Why does sexual violence occur in Islamic boarding schools? How is sexual violence prevented in Islamic boarding schools? The data collection process includes four stages, starting with the inclusion stage and the exclusion stage. This data was collected through the Google Scholar search engine using the keywords